(3EHOGd GdCOhjIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG (B: (3Gdbhd ai GdCHOGd HMSH eG CQi LRA ef CLRGA GdWH GdYXGe jSJMb Cf jNU hjaQO HcJGH s
(3BNQgG (B:s
(3YGaJ HOdg GdfbY ef GdMei GdMGOI fUa hRfg CeGQhf hfUa hRfg CeSfJjf Je HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B161 - (3U(B165s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B1 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThGQi edi (B(1538) s
Keywords: (3GdWHs